Controllability of Proportional Fractional Dynamical Systems - Vishnukumar, K. S.; Matar, M.; Govindaraj, V.; Balachandran, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this study, we explore the controllability of dynamical systems by applying proportional fractional derivatives. The Grammian matrix technique is employed to establish both necessary and sufficient conditions that govern the controllability of linear fractional dynamical systems. Additionally, utilizing Schauder’s fixed point theorem, we identify sufficient conditions for the controllability of nonlinear fractional dynamical systems. Numerous examples are provided to demonstrate and elucidate the theoretical findings.